Pengaruh Current Ratio, Debt To Equity Ratio, Dan Total Asset Turnover Terhadap Return On Asset Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2025 - Silvia Dwi Indriyani; Nuruddin Subhan (JURNAL MANAJEMEN PENDIDIKAN, 2026)
The Effect of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Return on Assets in Pharmaceutical Companies Listed on the Indonesia Stock Exchange for the 2021-2025 Period This study aims to analyze the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Return on Assets (ROA) in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. This research was motivated by the declining average Return on Assets of pharmaceutical companies in the post-pandemic period and the inconsistent findings of previous studies regarding the factors affecting corporate profitability.This research employed a quantitative research method using secondary data obtained from the annual financial statements of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used was purposive sampling, resulting in 11 companies that met the research criteria with a total of 55 observations during the 2021–2025 period. The data were analyzed using descriptive statistical analysis, panel data regression analysis, panel data model selection, classical assumption tests, and hypothesis testing with the assistance of EViews 13 software.The results indicate that the Fixed Effect Model (FEM) is the most appropriate panel data regression model for this study. Partially, Current Ratio (CR) has a positive and significant effect on Return on Assets (ROA). Likewise, Debt to Equity Ratio (DER) has a positive and significant effect on Return on Assets (ROA). Meanwhile, Total Asset Turnover (TATO) has no significant effect on Return on Assets (ROA). The Adjusted R-squared value of 0.876228 indicates that 87.62% of the variation in Return on Assets (ROA) can be explained by Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO), while the remaining 12.38% is explained by other factors outside the research model.